UPAYA MENINGKATKAN KREATIVITAS BELAJAR SISWA TEMA 2 SUBTEMA 1 MANFAAT TUMBUHAN BAGI KEHIDUPAN MANUSIA MENGGUNAKAN MODEL ROLE PLAYING DI KELAS III SD NEGERI 200217 PADANGSIDIMPUAN - Siregar, Dina Farikah; Lubis, Ilham Sahdi; Asmara, Sartika Rati; Zulfadli, Zulfadli; Sabri, Sabri (Jurnal Ilmiah Pendidikan Dasar (JIPDAS), 2024)
This study aims to improve the learning creativity of third grade students of SD Negeri 200217 Padangsidimpuan learning Theme 2 Subtheme 1 Benefits of Plants for Human Life by using the Role Playing Model. The type of research is Classroom Action Research (PTK) which is carried out in 2 cycles using the Role Playing learning model. Each cycle includes planning, action, observation and reflection stages. The subjects in the study were teachers and third grade students of SD Negeri 200217 Padangsidimpuan with a total of 16 students consisting of 4 male students and 12 female students. The instruments used in the study were questionnaire sheets and observation sheets. Data on the average value of student learning creativity in cycle I reached 53.25% can be included in the criteria "Very less creative”. While in cycle II the average value of student learning creativity 83.43% can be included in the criteria "Creative". So it can be concluded that the application of the role playing learning model can increase student learning creativity in learning theme 2 subtheme 1 the benefits of plants for human life in class III SD Negeri 200217 Padangsidimpuan